Analisis langkah jalan bulanan dan kalori yang dihasilkan pada pemahaman konsep energi dan metabolisme individu - Al Qindy, Wildan Hidayah; Damaira, Jihan Yusra; Siregar, Siti Hajar Leni (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study describes the association between the walking activity and then knowledge of energy concepts and metabolism in everyday life. This study utilized an embedded mixed methods design. Data on steps taken and calories consumed were recorded over a three month period (April-June 2025) using the Samsung Health application. The findings reveal fluctuations in physical activity, with particularly high levels occurring in May. The step count was shown to be positively associated with the calorie expenditure. Reflection revealed that the walks were a successful means of allowing the researchers to make sense of concepts of energy and metabolism. The present study finds that students can learn science during physical activity, and is a good method to narrow the theory and practice gap between the students’ life relation in the context of science learning gradually.